Edukasi dan Pelatihan Produksi Ekoenzim Berbasis Limbah Buah Pada Siswa SMPN 8 Kubu Raya - Apindiati, Rita Kurnia (Indonesian Journal Publisher, 2024)
Ecoenzymes are processed products resulting from fermentation of organic waste such as fruit and vegetable waste, as an effort to reduce waste into the environment. The lack of skills in processing organic waste into ecoenzymes is a problem that there are still large amounts of organic waste piled up, which has the potential to pollute air, air and soil. Community service with the topic of training on making ecoenzymes from fruit waste for students at SMPN 8 Kubu Raya aims to introduce students to the concept of environmental management from an early age, so that it can be applied in their lives both at home and school and in wider residential environments. Ecoenzymes can be used for various household purposes such as antiseptics and disinfectants in floor mopping, stain cleaners for washing dishes and clothes as well as insecticides and plant fertilizers. This PKM activity was attended by 30 students as activity participants, and was carried out using educational lecture methods and direct practice in making ecoenzymes. Monitoring during the activity and evaluation after the activity was completed showed that students had an understanding of managing organic waste into products that have many benefits, based on the ecoenzyme products resulting from each participant's practice. Apart from that, they also understand the materials and equipment used throughout the process stages in making ecoenzymes.